Multiply and divide - Sinclair, Karleen; Anderson, Greg; Heather, Warwick (Cairo Dar el farouk, 2004)
In this book , students will learn to make equal groups of objects equally they will also practise counting by 2s,5s and 10s up to100
Mathematics
8 12 13
Keywords: Mathematics